The role of food security in increasing adolescent girls' agency towards sexual risk taking: qualitative findings from an income generating agricultural intervention in southwestern Kenya - Maricianah A. Onono; Gladys Odhiambo; Lila Sheira; Amy Conroy; Torsten B. Neilands; Elizabeth A. Bukusi; Sheri D. Weiser (BMC, 2021)
Abstract Background Food insecurity is an important underlying driver of HIV risk and vulnerability among adolescents in sub-Saharan Africa. In this region, adolescents account for 80% of all new HIV infections. The primary purpose of this analysis is to understand perceived mechanisms for how a multisectoral agricultural intervention influenced sexual risk taking among HIV-affected adolescents in southwestern Kenya. Methods We conducted semi-structured, individual interviews with 34 adolescent-caregiver dyads who were participants in Adolescent Shamba Maisha (NCT03741634), a sub-study of adolescent girls and caregivers with a household member participating in the Shamba Maisha trial (NCT01548599), a multi-sectoral agricultural and microfinance intervention. Interviews were audiotaped, transcribed, translated, and analyzed using framework and interpretive description analysis methods. Results Adolescents receiving the Shamba Maisha intervention described no longer needing to engage in transactional sex or have multiple concurrent sexual partners as a way to meet their basic needs, including food. Key mechanisms for these effects include greater sexual agency among adolescent girls, and increased confidence and self-efficacy in overcoming existing reciprocity norms and sexual relationship power inequity; as well as staying in school. The intervention also increased caregiver confidence in talking about adolescent sexual reproductive health issues. In contrast, driven primarily by the need for food and basic needs, girls in the control arms described engaging in transactional sex, having multiple sexual partners, being unable to focus in school, getting pregnant or becoming HIV infected. Conclusion These findings emphasize the need to address food insecurity as a part of structural interventions targeting adolescent HIV risk in low-resource countries. We recommend that future interventions build upon the Shamba Maisha model by combining sustainable agricultural production, with household level interventions that deliberately target gender norms that contribute to unequal power dynamics.